2020
DOI: 10.1021/acs.est.0c05722
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification and Quantification of Microplastics in the Environment by Quantum Cascade Laser-Based Hyperspectral Infrared Chemical Imaging

Abstract: The monitoring of the emerging contaminant, microplastics, in the environment, in water supply, and for food safety is of major interest to science, consumers, and governments. While the chemical analysis of these particles is considered mandatory, a rapid and reliable method for the determination of particle sizes, shapes, and numbers is missing, as existing methods are not fitting into current laboratory measurement routines. In this study, we present an approach for circumventing these issues through the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 41 publications
0
56
0
Order By: Relevance
“…For both spectroscopic methods, the description and validation of the spectral identification routine have to be included. At present, it is common practice to report MP numbers in predefined size classes, i.e., in a binned form [10,54,81,128,129]. By this, the details on the size of each MP detected in samples get lost.…”
Section: Ways Of Reporting Results and Valuable Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…For both spectroscopic methods, the description and validation of the spectral identification routine have to be included. At present, it is common practice to report MP numbers in predefined size classes, i.e., in a binned form [10,54,81,128,129]. By this, the details on the size of each MP detected in samples get lost.…”
Section: Ways Of Reporting Results and Valuable Informationmentioning
confidence: 99%
“…These were subsequently scanned in the region 1800-1184 cm −1 and 1160-1084 cm −1 to identify the targeted polymer types. They compared the QCL-IR system's performance to stateof-the art FTIR imaging and concluded that the results gained using QCL-IR microscopy were in good agreement with those of the reference method, while being about tenfold as fast [81]. QCL-IR, until now, was successfully applied to samples of soil [82,83], river [84], and brackish waters [85].…”
Section: Analysis (Fourier Transform) Infrared (Ft)ir Spectroscopymentioning
confidence: 95%
See 1 more Smart Citation
“…With regards to innovative technologies addressing the isolation, identification and quantification of NMPs that cause risks for human health, different combinations of methods are currently under research for targeting different size ranges. For MP particles down to 1 μm, techniques employing a correlative combination of light microscopy or hyperspectral imaging with identification by laser confocal Raman and TOF-SIMS are under development [78][79][80]. For plastic particles in the nanoscale, correlative scanning electron microscopy (SEM) -confocal Raman spectroscopy has being explored [81,82].…”
Section: Pioneering Technologiesmentioning
confidence: 99%
“…Oxoanions are a class of pollutants of increasing concern resulting from various industrial processes prevalent today. When discharged into bodies of water, their inherent toxicity harms ecosystems and contaminates potable water. , Oxoanions have been classified as toxic priority pollutants under the Clean Water Act, and because tolerable concentrations are often exceeded, targeted treatment of affected bodies of water becomes necessary. , Several treatment mechanisms have been developed to remediate water sources from these pollutants ranging from the facilitation of degradation processes and use of activated carbon capture to the deployment of sorbents (such as metal–organic and covalent–organic frameworks) for explicit removal of oxoanions. The latter approach is the focus of this investigation, for which high capacity, porous materials including metal–organic frameworks (MOFs) have found efficient implementation as sorbents. , MOFs (nanoporous crystalline materials consisting of metal clusters linked together by organic ligands) exhibit tunable pore sizes, easily functionalizable ligands, and high internal surface areas, making them ideal candidates for small molecule capture and separation. The vast combinations of metal nodes and organic ligands allow for tuning the chemical and physical properties of MOFs to highly specific applications . This flexibility has led to a wide range of MOF designs, such as zeolitic imidazolate frameworks (ZIFs), cationic MOFs, and neutral MOFs containing open-metal sites. MOFs hold much promise as highly selective next-generation sorbents by virtue of their diverse structures and finely tunable host–guest interactions.…”
mentioning
confidence: 99%